Challenges and tradition: Exploring the communication concept of pamali about pregnant mother in Lakang Island society, Makassar - Yulianandaris, Yulianandaris; Munajat, MD Enjat; Yustikasari, Yustikasari; Novianti, Evi (Universitas Bunda Mulia, 2025)
Lakkang Island has a beautiful tourist destination and cultural diversity which is also the center of attention and attraction for tourists. This place still implements culture in the form of traditions/customs. The local community still strongly adheres to the customs or beliefs called Pamali or commonly called Kasimpalli, which have been entrenched for generations. However, some of the immigrant communities who live there have adapted to appreciate and respect the traditions of the local community so that their friendship remains good even others don't quite believe it pamali. This type of research uses descriptive qualitative. Qualitative method because pamali is a non-exact object that can only be described in words. Researchers used a descriptive approach to describe the various ways the pamali concept was applied in the Lakkang Island Community. The data collection process was assisted by traditional leaders and the Lakkang Island Community. The methods used to collect data were interviews, observation, documentation, audio visual. Pamali in the Lakkang Island Society, is defined as expressions that contain a kind of prohibition or prohibition to be carried out because they contain consequences. Even though times have changed, the people do not want to let go of this sacred tradition, making pamali still exist and have a high position for the indigenous people of the island itself. From a cultural perspective, belief in pamali is seen as a way to maintain traditions that have been passed down by previous generations.Keywords: Culture; Pamali; Tourism; Lakkang Island